What makes Americans fall behind in their finances? Evidence from the national well-being survey - Miloș, Laura Raisa; Miloș, Marius Cristian; Barna, Flavia Mirela; Boțoc, Claudiu (Frontiers in Psychology, 2023)
The question of how often Americans fall behind on their finances is analyzed using the National Financial Well-Being survey of the United States Consumer Financial Protection Bureau. An ordered logit model is proposed to study the effect of individual and household characteristics on the likelihood of falling behind in one’s finances. The analysis shows that traditional variables such as income, age, education, and health are statistically significant predictors of falling behind in one’s finances. In addition, the study shows that the volatility of income, saving habits, and individuals’ financial knowledge significantly contribute to the explanation of Americans’ economic behavior.